The Interdecadal Change of Relationship Between Summer Water Vapor Content Over Tibetan Plateau and Spring Sea Surface Temperature in Indian Ocean - Ren, Qian; Zhong, Shanshan; Chen, Dan; Li, Xiang; Zhang, Tangtang (Frontiers in Earth Science, 2020)
The interannual relationship between the spring SST over the western tropical Indian Ocean (WTIO SST) and summer water vapor content over Tibetan Plateau (TPWVC) enhances significantly after 1992/1993. The regressed atmospheric circulation against WTIO SST index (WTIO SSTI) for two periods are explored to explain the interdecadal variation. During ID1 (1979-1991), the center of the anomalous anticyclone is generally located eastward and the weak easterly anomalies on its southern flank transport moisture from the western Pacific to Southeast China with no effects on TPWVC. In ID2 (1994-2017), the Northwest Pacific anticyclone, the anomalous easterlies and the subtropical high at 500 hPa all move westward and enhance significantly, thus it forms a westward moisture transport pathway delivering the water vapor from the western Pacific into Tibetan Plateau (TP). A possible mechanism is raised. On one hand, the SST anomalies (SSTA) related to WTIO SSTI extend eastward from spring to summer in ID2. With the increased mean SST in the Indo-western Pacific Ocean under the global warming and the stronger mean summer SST in the eastern Indian Ocean, the positive SSTA induce the enhanced Kelvin waves and Northwest Pacific anticyclone with strong easterly anomalies during ID2. But in ID1, the SSTA related to WTIO SST confined in the western-central Indian Ocean from spring to summer excite the decreased Kelvin waves with less significant easterly anomalies due to the weaker mean SST. On the other hand, the eastward shift of tropical summer SSTA generate the increased convection and rising motion over the Southeast Indian Ocean in ID2. They enhance the easterly anomalies on the southern flank of the Northwest Pacific anticyclone and induce anticyclonic shear through the meridional circulation. As a result, the easterly anomalies shift westward to transport more moisture into TP. However, in ID1, the easterly anomalies of the anticyclone cannot be strengthened with no westward shift. Therefore, the above reasons lead to the interdecadal enhancement of relationship between the spring WTIO SST and summer TPWVC.